Joseph Schumpeter, Alfred Marshall and the nature of restless capitalism - Stan Metcalfe (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2024)
This lecture explores the evolution of economics as a discipline during 1870-1920, focusing on the critical question of wealth creation from knowledge. It highlights the tension between understanding economic structures and their transformative growth, with special attention to Alfred Marshall and Joseph Schumpeter's insights on the evolving nature of capitalism and innovation's role in economic development. By contrasting their views — Schumpeter's emphasis on disruptive innovation and Marshall's on gradual change — the lecture underscores the significance of innovation and knowledge in driving economic transformation. This discussion aims to illuminate the complex relationship between knowledge, innovation, and economic dynamics, essential for understanding the workings of modern economies.
Keywords: 330; Economic Evolution; Innovation and Growth; Schumpeter and Marshall; Wealth from Knowledge; Historical Economics